Description and Analysis of a Novel Subtype of the Anti-Synthetase Syndrome Characterized by Frequent Attacks of Fever and Systemic Inflammation in a Single-Center Cohort Study - Sun, Shuhui; Chen, Zhiwei; Zhang, Danting; Xu, Wenwen; Wu, Wanlong; Sun, Fangfang; Gu, Liyang; Chen, Jie; Li, Jiajie; Li, Ting; Wang, Xiaodong; Ye, Shuang (Frontiers in Immunology, 2021)
Abstract Objectives: The aim of this study was to investigate anti-synthetase syndrome (ASyS) patients who presented with recurrent episodes of fever and systemic inflammation. Methods: A retrospective cohort of Chinese ASyS patients (n=126) in our center (between January 2013 and January 2020) was included. Patients presenting with concomitant autoimmune rheumatic diseases or malignancies were subsequently excluded. The number of noninfectious fever attacks and attack frequency were recorded and calculated. Patients with two or more attacks and within the upper 3 quartiles of attack frequency were defined as high-inflammation group. Univariate and multivariate analyses were carried out to characterize the high-inflammation subtype. Results: Out of 113 eligible patients with an average of 5 years follow up, 25 patients were defined as the high-inflammation group (16 for anti-Jo1, 9 for anti-PL7), with an average of 1.12 attack/patient-year. Compared to low-inflammation group (0-1 attack only and a frequency lower than 0.5 attack/patient-year), the high-inflammation group had higher occurrence of fever and rapid progressive interstitial lung disease (RPILD) as the first presentation (84% vs. 21% and 40% vs. 9%, respectively, both p<0.01). Anti-PL-7 was related to the more inflammatory phenotype (p=0.014). Cumulative disease-modifying agent exposures (>=3) were much higher in the high-inflammation group (60% vs. 26%), while biological agents, i.e., rituximab and tocilizumab, showed better ‘drug survival’ for Jo-1+ and PL-7+ ASyS patients with high inflammation, respectively, in our cohort. Conclusions: ASyS with recurrent systemic inflammatory episodes reflects a subtype of more aggressive and refractory disease in the spectrum of ASyS. Increased awareness of this subtype might lead to more appropriate management.